Gelofusine Attenuates Tubulointerstitial Injury Induced by cRGD-Conjugated siRNA by Regulating the TLR3 Signaling Pathway - Bohong Cen; Wenjie Liao; Zhen Wang; Linyuan Gao; Yuanyi Wei; Wen Huang; Shuai He; Wei Wang; Xiaoxia Liu; Xinghua Pan; Aimin Ji (Elsevier, 2018)
Integrin αvβ3, which is selectively targeted by cyclic arginine-glycine-aspartic acid (cRGD) peptides, is significantly upregulated in tumors. Previous studies showed that small interfering RNA (siRNA) modified with cRGD (cRGD-siRNA) could significantly inhibit tumor growth through RNAi with oncogene expression. However, cRGD-siRNA is partially reabsorbed and trapped in the kidneys, causing renal injury in an unpredictable manner. This study aimed to investigate the influence of Gelofusine on tubulointerstitial injury induced by cRGD-siRNA in vitro and in vivo. The effect of Gelofusine on the distribution of cRGD-siRNA in tumor-bearing nude mice and wild-type mice was also explored. We found that Gelofusine inhibited apoptosis and activation of the innate immune response of human tubular epithelial cells induced by cRGD-siRNA in vitro. In addition, co-injection of Gelofusine efficiently reduced renal retention of cRGD-siRNA without affecting its tumor targeting in vivo. Further in vivo studies indicated that Gelofusine significantly attenuated tubulointerstitial injury induced by cRGD-siRNA through regulating Toll-like receptor 3 (TLR3)-mediated activation of the nuclear factor κ B (NF-κB) and caspase-3 apoptotic pathway. In conclusion, Gelofusine, acting as a novel and effective renal protective agent, could form a compound preparation with siRNA drugs for future clinical applications.